The influence of word wall on students' interest and learning outcomes - Alfina Hidayaty; Mahwar Qurbaniah; Anandita Eka Setiadi (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2022)
A word wall is a fun, entertaining learning media game. This study aims to determine the effect of word wall media on student interest and learning outcomes. The research used the experimental method, Quasi Experimental form with Nonequivalent Control Group Design. Determination of the experimental and control classes using a simple random sampling method, treatment in the experimental class using word wall media, and media box questions in the control class. The data collection instrument for pretest-posttest learning outcomes is in the form of multiple-choice questions. Meanwhile, interest in learning was measured using a questionnaire with the Linkert scale. Analysis of learning interest data using the t-test obtained the value of student interest in learning (0.000 <0.05). The value of student learning outcomes based on the U-Mann Whitney test obtained a value of (0.000 <0.05), and the effect size of the results showed that the media word wall affects an interest in learning by 58.9% with an effect size value of 1.1 (large). The highest learning interest indicator is feeling happy, with a percentage of 71% in the experimental class. The effect of word wall media on learning outcomes is 79.4%, and the effect size value is 1.9 (large). The completeness value of the posttest in the experimental class was 89%, while in the control class, the percentage of completeness was 45%. It is concluded from this research that there are differences and the influence of word wall media on students' interests and learning outcomes. Pengaruh penggunaan word wall terhadap minat dan hasil belajar siswaWord wall merupakan media pembelajaran yang menyenangkan dan menghibur. Penelitian ini bertujuan untuk mengetahui pengaruh media word wall terhadap minat dan hasil belajar siswa. Metode penelitian menggunakan eksperimental dengan desain Nonequivalent Control Group Quasi Experimental. Penentuan kelas eksperimen dan kontrol menggunakan metode simple random sampling, dengan perlakuan penggunaan media word wall pada kelas eksperimen dan kotak soal pada kelas kontrol. Instrumen pengumpulan data untuk pretest-posttest hasil belajar berupa soal pilihan ganda. Minat belajar diukur menggunakan kuesioner dengan skala Linkert. Analisis data minat belajar menggunakan uji t diperoleh nilai minat belajar siswa 0,000 < 0,05. Nilai hasil belajar siswa berdasarkan uji U-Mann Whitney adalah 0,000 < 0,05, dan effect size hasil menunjukkan bahwa media Word wall mempengaruhi minat belajar sebesar 58,9% dengan nilai effect size sebesar 1,1 (besar). Indikator minat belajar tertinggi adalah merasa senang, dengan persentase 71% pada kelas eksperimen. Pengaruh media Word wall pada hasil belajar mencapai 79,4%, dan nilai effect size sebesar 1,9 (besar). Nilai ketuntasan pada posttest pada kelas eksperimen mencapai 89%, sedangkan pada kelas kontrol persentase ketuntasan sebesar 45%. Dapat disimpulkan bahwa terdapat perbedaan dan pengaruh media wor dwall terhadap minat dan hasil belajar siswa